Effects of BiMO3 on dielectric, ferroelectric, and piezoelectric properties of perovskite lead‐free piezoelectric BaTiO3–(Bi0.5Na0.5)TiO3 ceramics. Issue 4 (25th April 2017) - Chaiyo, Nopsiri; Muanghlua, Rangson; Vittayakorn, Wanwilai; Vittayakorn, Naratip
Abstract: New lead‐free piezoelectric ceramics of 0.9BaTiO3 –(0.1− x )(Bi0.5 Na0.5 )TiO3 – x Bi M O3, M =Al and Ga, where x =0.00‐0.10, were fabricated by the solid‐state reaction technique. The effect of Bi M O3 contents on the perovskite structure, phase transition, and dielectric, ferroelectric, and piezoelectric properties was investigated. X‐ray diffraction patterns showed that the ceramics exhibit a monophasic perovskite phase up to x =0.06, suggesting stabilized perovskite structures with B‐site aliovalent substitutions. Compositional‐dependent phase transitions were observed from tetragonal to pseudo‐cubic phase with increasing Bi M O3 amounts. Al 3+ ions were found to stabilize the transition temperature of the ceramics, while significantly decreasing transition temperature, and a change in the dielectric peak were found with an increasing amount of Ga 3+ . Regarding Al 3+ substitution, the remanent polarization ( P r ) values were found to decrease slightly with the Al 3+ amount. With regard to Ga 3+ substitution, P r values decreased with the Ga 3+ amount up to 0.06 and then increased slightly. The ceramics became softer with a higher degree of substitution according to the lower coercive field ( E c ), when compared with 0.9BaTiO3 –0.1(Bi0.5 Na0.5 )TiO3 ceramics. Ceramics with a lower degree of substitution and tetragonal phase showed butterfly strain loops that correlated with normal ferroelectric behavior.